First principles study of the electronic, optical, elastic and thermoelectric properties of Nb2WNi alloy. (18th June 2021) - Güler, M.; Uğur, Ş.; Uğur, G.; Güler, E.
Abstract : We performed density functional theory (DFT) calculations to explore the electronic, optical, elastic and thermoelectric properties of Nb2 WNi alloy for the first time by addressing the two different crystal structures (Cu2 MnAl and Hg2 CuTi) of the alloy. The calculated elastic constants results prove the mechanical stability for both crystal structures of the alloy. As well, Nb2 WNi shows ductility for both crystal structures with a dominant metallic character. Nb2 WNi alloy can be a good reflector, in particular for practical vacuum UV applications. It has also a high refractive index, especially in the IR region. The optical conductivity results support the use of Nb2 WNi alloy for IR solar cell applications. The computed Seebeck coefficient values suggest the potential of Nb2 WNi alloy as new thermoelectric material. GRAPHICAL ABSTRACT: UF0001